The rodent model of impaired gastric motility induced by allyl isothiocyanate, a pungent ingredient of wasabi, to evaluate therapeutic agents for functional dyspepsia - Kazuki Hashimoto; Kimihito Tashima; Taku Imai; Kenjiro Matsumoto; Syunji Horie (Elsevier, 2021)
Functional dyspepsia (FD) is thought to be mainly based on gastric motility dysfunction and chronic hypersensitivity, yet FD animal models has been reported a few. We studied to establish the mouse model of impaired gastric motility induced by a pungent ingredient of wasabi allyl isothiocyanate (AITC), which is reliable to evaluate prokinetic agents. Male ddY mice were used. Gastric motility was measured by 13C-acetic acid breath test in conscious mice. AITC (80 mM) was given 60 min before the measurement of motility. Prokinetic agents including itopride (30, 100 mg/kg), mosapride (0.1-1 mg/kg), neostigmine (30 μg/kg), acotiamide (10-100 mg/kg), and daikenchuto (100-1000 mg/kg) were given 40 min before the measurement. AITC impaired gastric motility without mucosal damages, which reverted 24 h after AITC treatment. The decreased motility induced by AITC was restored by prokinetic agents such as itopride, mosapride, neostigmine, and acotiamide. In separate experiment, daikenchuto recovered the decreased motility induced by AITC, although daikenchuto had no effect on motility in normal condition. In conclusion, it is considered that the AITC-induced impaired gastric motility mouse model is useful to develop new prokinetic agents for treatment of FD, and to re-evaluate traditional Japanese herbal medicines.